Empyema in Extradural Hematoma As a Cause of Hypodense Extradural Hematoma - Prabhuraj, A. R.; Shukla, Dhaval (Indian Journal of Neurotrauma, 2015)
The causes of hypodensity in an extradural hematoma (EDH) are air, active bleeding, or chronic blood. A hypodense EDH due to secondary infection and empyema formation is not described. We describe a case of hypodense EDH due to empyema. A 24-year-old man presented 12 days after injury with headache. He was asymptomatic after injury and did not have fever. Computed tomography (CT) scan of the head revealed hypodense extradural collection in temporoparietal region with mass effect. He underwent craniotomy and evacuation of extradural lesion. The surgical findings were pus mixed with old blood. The final diagnosis was empyema within EDH.
Keywords: extradural hematoma; extradural empyema; extradural abscess